Kesıapan Madrasah Mengımplementasıkan Kurıkulum Merdeka di MIN 2 Bantul - wijayanti, inggit; Intan Nur Ngazizah (Jurnal Elementaria Edukasia, 2023)
Curriculum changes that are happening at this time are the implementation of the independent curriculum in several education units with a pilot project system, one of which is MIN 2 Bantul. With this the school as the spearhead in carrying out the implementation curriculum must be able to understand and apply it to the fullest because the quality of the implementation of the educational process is one of them by looking at the success rate of implementation. The purpose of this study is to describe the readiness of madrasa teachers in implementing the independent curriculum at MIN 2 Bantul. The research method is descriptive qualitative. The research samples were class I and IV teachers at MIN 2 Bantul, data collection was carried out through interviews, observation and documentation. The results of the study showed that the readiness of madrasa teachers in DIY in implementing the independent curriculum was quite ready. What the teacher did in preparing for implementation was understanding the characteristics of changes in the independent curriculum, reviewing and comparing learning outcomes and teacher and student books, analyzing learning abilities by setting goals. learning and the flow of learning objectives, developing new tools, and understanding the independent curriculum assessment. In this case the school facilitates teachers to carry out technical guidance held by religious decrees or from external services and teachers carry out independent learning related to the independent curriculum through several platforms that have been provided